Forms of Transnational Economic Cooperation and Integration in the Baltic Region - Mikhaylov, Andrey S.; Bolychev, Oleg N. (International Journal of Economics and Financial Issues, 2015)
The Baltic macro-region is a heterogeneous socio-economic ecosystem consisting of both the innovative and successful ‘core regions’ and the peripheral areas of the borderland. Facing contemporary challenges of the global market competition, national policies are increasingly being directed at establishing conjoint competence centers capable of absorption and recombination of heterogeneous tacit and codified knowledge generated by the nodes of an international innovation network. Furthermore, systematic and sustainable institutional efforts on facilitating the embeddedness of the remote and underdeveloped areas into these networking activities have created a diversity of transnational economic cooperation and integration (TECI) forms being elaborated and applied by the institutions of the respective territories. Drawing on an in-depth review, the study reflects on the development factors relevant to an active integration and cooperation process of individual territories of the respective countries. The study suggests that social, cultural, institutional proximity facilitates industrial collaboration being of the highest significance in increasing competitive advantage of a territory. Keywords: cross-border cooperation, Baltic region, regionalization, new regionalism, Russia JEL Classifications: F15, F63, O19, R10